2017
DOI: 10.1080/11038128.2017.1293155
|View full text |Cite
|
Sign up to set email alerts
|

Sensor technology more than a support

Abstract: The results indicate that sensor technology has potential to increase opportunities for persons with memory impairment to perform and participate in activities and to unburden their partners. The results may promote an understanding of how sensor technology can be used to support persons with memory impairment in their homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The most common form of bias was selection bias. Examples of selection bias were all: participants had experience with technology [23], same site [25,28,30,34], or a disproportionately large sample that was male [22,30,36]. These examples of bias limit the external validity of the results.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common form of bias was selection bias. Examples of selection bias were all: participants had experience with technology [23], same site [25,28,30,34], or a disproportionately large sample that was male [22,30,36]. These examples of bias limit the external validity of the results.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…These studies all came from single originations: Australia, Scotland, Canada, United Kingdom, United Kingdom/Italy/Malaysia, Spain, Netherlands, Germany/Belgium, and Taiwan. The theme increased independence (keeps PWD home longer, helps structure everyday events) occurred in 7/68 occurrences (10%) [3,30,40,46,51,53,59]. Three of these studies originated from Sweden, and two were from Canada, while the rest were from single originations: Netherlands, Netherlands/Germany/Belgium.…”
Section: Facilitators To the Adoption Of Atmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, out of 34 studies, we found that 16 studies represented proof-of-concept, acceptability, and/or feasibility testing for technologies that are new and have not been used in the dementia population previously. These studies demonstrated some usability issues for smart home and assistive systems, e.g., technological malfunctions and general user-unfriendliness; however, the technology used was predominantly non-intrusive and well-accepted (Hattink et al, 2016;Olsson et al, 2018).…”
Section: Discussionmentioning
confidence: 96%